2016
DOI: 10.3389/fpsyg.2016.00002
|View full text |Cite
|
Sign up to set email alerts
|

Songs for the Ego: Theorizing Musical Self-Enhancement

Abstract: This paper outlines a theoretical account of musical self-enhancement. I claim that listening to music serves as a resource for actively manipulating affective states so that a positive self-view is maintained and a sense of optimism is provided. Self-enhancement—the process by which individuals modify their self-worth and gain self-esteem—typically takes place in social interactions. I argue that experiencing music may serve as a unique “esthetic surrogate” for interaction, which equally enables self-enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 96 publications
(126 reference statements)
3
40
0
Order By: Relevance
“…Generally, experiences of mastery and accomplishment serve as a boost to the adolescents' perception of self-efficacy, which in turn inform the perception of agency in the short-term and foster the development of agency in the medium-and long-term (Bandura, 1982(Bandura, , 2005Zimmermann and Cleary, 2005). Music has been proposed as one resource that successfully leads to feeling empowerment (i.e., the reinforcement of efficacy beliefs; Wallace-DiGarbo and Hill, 2006) and self-enhancement (i.e., the tendency to evaluate oneself positively; Elvers, 2016). found that power-related emotions (self-determination, independence, daring, freedom, strength, empowerment, rebelliousness, and unconstrained feeling) were the second strongest factor out of six explaining music-related pleasure in the participants' everyday life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, experiences of mastery and accomplishment serve as a boost to the adolescents' perception of self-efficacy, which in turn inform the perception of agency in the short-term and foster the development of agency in the medium-and long-term (Bandura, 1982(Bandura, , 2005Zimmermann and Cleary, 2005). Music has been proposed as one resource that successfully leads to feeling empowerment (i.e., the reinforcement of efficacy beliefs; Wallace-DiGarbo and Hill, 2006) and self-enhancement (i.e., the tendency to evaluate oneself positively; Elvers, 2016). found that power-related emotions (self-determination, independence, daring, freedom, strength, empowerment, rebelliousness, and unconstrained feeling) were the second strongest factor out of six explaining music-related pleasure in the participants' everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…In the conceptual model of health-relevant competencies in music, Saarikallio (2017Saarikallio ( , 2019a argues that engaging in musical behaviors can foster emotional health when the emotions expressed, evoked, and regulated through music are surrounded by (a) self-reflective awareness and (b) sense of self-control and agency. Concerning musical self-enhancement, Elvers (2016) proposed a framework according to which there are three main musical experiences bolstering positive self-evaluations: induction of empathy (through identification with the music, self/other merging, and self-confirmation), promotion of social cohesion (through rhythmic entrainment and reinforcement of a cultural worldview and sense of social belonging), and pleasure (through the induction of positive affect, default mode networkactivation, and self-referential emotions). According to Elvers, this framework encompasses "the kind of musical experiences that elicit positive affect related to the self, that induce feelings of power and control, that promote positive self-evaluations, and ultimately promote self-esteem" (Elvers, 2016, p. 3).…”
Section: Music-fostered Agency and Wellbeingmentioning
confidence: 99%
“…Accordingly, it seems that, as with the musicians and their instrument, these cases are similar instances of emotional self-stimulation. Via iterative cycles of motor entrainment and synchronization that unfold in response to musical dynamics, auditory properties of the music directly modulate a cascade of emotion-specific neural and physiological responses, coaxing emotions out of us and regulating their dynamics in real time as they unfold over short-and long-term listening episodes (Elvers, 2016;Fritz et al, 2013;Lundqvist, Carlsson, Hilmersson, & Juslin, 2009;Witek, Clarke, Wallentin, Kringelbach, & Vuust, 2014). And these musical feedback loops seed functional gain.…”
Section: Exe and Materials Culturementioning
confidence: 99%
“…And these manipulations loop back onto us, shaping our future manipulations and responsive behavior. Auditory properties of the music directly modulate a cascade of affect-driving neural and physiological responses, coaxing experiences out of us and regulating their embodied dynamics in real-time over short and long-term listening episodes (Elvers 2016;Witek et al 2014). When integrated with musical technologies this way, musical-affective feedback loops scaffold access to experiences and regulatory capacities that might otherwise be inaccessible-even from the earliest stages of life (Krueger 2013a).…”
Section: Materials Scaffoldingmentioning
confidence: 99%